Laser spectroscopy of the ground-state hyperfine structure in H-like and Li-like bismuth. (29th January 2015) - Vollbrecht, J; Andelkovic, Z; Dax, A; Geithner, W; Geppert, C; Gorges, C; Hammen, M; Hannen, V; Kaufmann, S; König, K; Litvinov, Y; Lochmann, M; et al.
Abstract: The LIBELLE experiment performed at the experimental storage ring (ESR) at the GSI Helmholtz Center in Darmstadt aims for the determination of the ground state hyperfine (HFS) transitions and lifetimes in hydrogen-like ( 209 Bi 82+ ) and lithium-like ( 209 Bi 80+ ) bismuth. The study of HFS transitions in highly charged ions enables precision tests of QED in extreme electric and magnetic fields otherwise not attainable in laboratory experiments. While the HFS transition in H-like bismuth was already observed in earlier experiments at the ESR, the LIBELLE experiment succeeded for the first time to measure the HFS transition in Li-like bismuth in a laser spectroscopy experiment.